Mitigating barriers to cross-border commuting and increasing institutional trust via EU b-solutions initiative - Medeiros, E.; Guillermo-Ramirez. M. (2021 Barcelona workshop on regional and urban economics. Internal migrations and cross-border commuting, 2021)
For more than six decades the European Union (EU) has promoted, one way or the other, systematic European Territorial Integration, understood as process of reducing all sorts of cross-border barriers. Already known as the year Earth changed, 2020 inverted this process via generalised implementation of covidfencing measures across European national borderlines. A wealth of literature has already been published on the direct and indirect covidfencing negative impacts from cross-border commuters along the several phases of covid-19 lockdowns in Europe. In this context, this article is centred in debating the role of the EU b-solutions initiative to facilitate cross-border commuting in Europe and to mitigate potential future pandemic scenarios leading to a systematic shutdown of national borders. In a complementary manner, the article debates the potential role of b-solutions to cement institutional trust in post-pandemic cross-border cooperation. Finally, the research proposes a theoretical framework aiming at analysing the relation between cross-border commuting and cross-border barriers, to better unveil potential positive developments for EU cross-border commuting after the COVID-19 era. The paper concludes that the EU b-solutions initiative is paving the way for reducing all sorts of administrative border barriers in Europe, and therefore cross-border commuting. However, it needs a wider implementation across all European national borders to expand its positive impacts. It also demonstrates the crucial positive role that b-solutions has had to robust institutional trust by, for instance, fomenting the involvement of local and regional authorities across borders in defining and analysing common challenges jointly, but also involving some cross-border entities in the identification and analysis of specific obstacles.